2017
DOI: 10.1159/000454857
|View full text |Cite
|
Sign up to set email alerts
|

Dermoscopy of Granuloma Annulare: A Clinical and Histological Correlation Study

Abstract: Background: Dermoscopy of granuloma annulare has been investigated by several studies, but none of them took into account the variability of dermoscopic findings according to clinical characteristics and/or histological subtype. Objective: To describe the dermoscopic features of classic granuloma annulare and seek possible dermoscopic clues related to specific clinical findings/histological subpatterns. Methods: A representative dermoscopic image of a target lesion (the most active lesion underwent histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 31 publications
0
35
1
3
Order By: Relevance
“…The detection of the above-mentioned dermoscopic findings may come in very handy even to differentiate both morphea and CLS from other similar dermatoses, mainly including: granuloma annulare (patchy type), typically displaying blurry vessels having variable morphology, white areas, and yellowish-orange structureless areas (in "palisading granuloma" histological subtype) [22]; fixed drug eruption, usually featuring a reddishpurple background and brownish peppering (in longstanding lesions) [pers. observations]; mycosis fungoides, which is characterized by fine short linear vessels, orange-yellowish patchy areas and spermatozoa-like vessels [35]; necrobiosis lipoidica, commonly displaying comma-shaped (incipient lesions), network-shaped/ hairpin-like (more developed lesions), or elongated, branching, and focused serpentine (advanced lesions) vessels over a yellowish-orange/whitish-pinkish background (with or without reddish areas) [7,20]; sarcoidosis/lupus vulgaris, often showing structureless yellowish-orange areas as well as focused linear-branching vessels [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The detection of the above-mentioned dermoscopic findings may come in very handy even to differentiate both morphea and CLS from other similar dermatoses, mainly including: granuloma annulare (patchy type), typically displaying blurry vessels having variable morphology, white areas, and yellowish-orange structureless areas (in "palisading granuloma" histological subtype) [22]; fixed drug eruption, usually featuring a reddishpurple background and brownish peppering (in longstanding lesions) [pers. observations]; mycosis fungoides, which is characterized by fine short linear vessels, orange-yellowish patchy areas and spermatozoa-like vessels [35]; necrobiosis lipoidica, commonly displaying comma-shaped (incipient lesions), network-shaped/ hairpin-like (more developed lesions), or elongated, branching, and focused serpentine (advanced lesions) vessels over a yellowish-orange/whitish-pinkish background (with or without reddish areas) [7,20]; sarcoidosis/lupus vulgaris, often showing structureless yellowish-orange areas as well as focused linear-branching vessels [3][4][5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the histopathological correlation of dermoscopic features has not been investigated. The lack of such evidence represents a significant limitation as it is well known that cutaneous disorders presenting clinical/histological heterogeneity may display different dermoscopic findings based on disease stage, and the use of dermoscopy is really helpful only when this technique may provide additional information which is not visible on clinical grounds and correlates with significant pathological findings [3][4][5][6][7]22].…”
mentioning
confidence: 99%
“…Interestingly, similar granulomatous dermatoses which enter into the differential diagnosis typically lack central homogeneous reticular well-focused vessels and display different dermoscopic findings, thus facilitating their distinction. 2,3 In particular, annular sarcoidosis classically features yellowish-orangish structureless areas as well as wellfocused linear or branching vessels, 2,3 granuloma annulare commonly shows yellowish-orangish areas ("palisading granuloma" histological subtype), whitish structures and blurry vessels having variable appearance (dotted, linearly irregular and branching), 2,3 and necrobiosis lipoidica typically displays serpiginous, branching, well-focused vessels over a yellowishorangish/whitish-pinkish background whose diameter decreases toward the periphery of the lesion. 2,3 In conclusion, dermoscopy may be useful to assist the diagnosis of AEGCG and its differentiation from similar granulomatous conditions.…”
Section: Dermoscopy In Annular Elastolytic Giant Cell Granulomamentioning
confidence: 99%
“…There is no published literature on dermoscopy of PNGD. However, dermoscopy of other necrobiotic disorders such as granuloma annulare has shown that yellowish‐orange structureless areas correspond to palisaded granuloma and whitish areas to collagen degeneration . The similarities and differences between other clinical and dermoscopic differentials and PNGD are shown in Table .…”
Section: Clinical Dermoscopic and Histological Features Of Cutaneousmentioning
confidence: 99%
“…However, dermoscopy of other necrobiotic disorders such as granuloma annulare has shown that yellowish-orange structureless areas correspond to palisaded granuloma and whitish areas to collagen degeneration. 3,4 The similarities and differences between other clinical and dermoscopic differentials and PNGD are shown in Table 2. A clinical possibility of PNGD should be considered in lesions demonstrating yellowishorange structureless areas with prominent keratin plugs on dermoscopy.…”
mentioning
confidence: 99%